PRINSIP-PRINSIP PENGEMBANGAN IPTEK DALAM PERSPEKTIF ISLAM SERTA KORELASINYA DENGAN PEMBELAJARAN ABAD 21 DAN PENDEKATAN SAINTIFIK - Nurlisma (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Science and technology equip humans to carry out worship to Allah, human civilization is very dependent on science and technology. Thanks to these advances, the fulfillment of human needs can be done faster and easier. The influence of the development of science and technology has a positive and negative impact, the positive impact is the more open and the spread of information and knowledge from and around the world quickly, while the negative impact is a change in values, norms, rules and morals of life adopted by the community. The development of learning will always be closely related to the situation, progress, social and rapid scientific progress. The digitalization era requires teachers to have skills in quality, meaningful, creative, innovative, interesting and exciting learning. Thus, teachers are required to develop competencies, especially in assembling the conceptualization of learning and mastery of IT in order to realize the change of civilization towards a generation of knowledge (knowledge society). This requires us to master 21st century skills, namely being able to understand and utilize information and communication technology (ICT Literacy Skill), be able to utilize technology and media, communicate effectively, think logically and critically to be able to provide various solutions to problems in learning and collaborate intensely. In an effort to provide students with the feel of 21st century learning, the learning process is encouraged to apply a scientific approach or a scientific approach.